OPPORTUNITIES OF IMMUNOMODULATORY AGENT BASED ON BACTERIAL LYSATES MIXTURE IN PEDIATRIC PRACTICE - S.I. Erdes; S.A. Revyakina ("Paediatrician" Publishers LLC, 2010)
The results of clinical studies of bacterial lysates mixture (Imudon) efficacy in pediatric practice are analyzed. Obtained data show reasonability of the drug administration in children with recurrent respiratory diseases, pharyngeal and tonsil infections, herpetic stomatitis, acute laryngitis and tonsils extraction. Key words: children, bacterial lysates mixture, clinical trial, review. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):63-68)